The Effect of Communication and Teamwork on Employee Performance with Employee Satisfaction as an Intervening Variable at at BPJS Pematang Siantar Branch Office and Padang Sidimpuan Branch Office - Dewi Sartika Sitepu; Muhammad Isa Indrawan (Lafadz Jaya Publisher, 2024)
Basically, human resources remain a valuable resource and an obstacle that must be overcome by the business world in the era of globalization. Human dignity is a factor that contributes to the successful and effective operation of an organization. The phenomenon that occurs at BPJS Employment at the Pematang Siantar and Padang Sidimpuan Branch Offices is a lack of communication between employees so that misunderstandings often occur in work, this occurs because of poor teamwork between employees so that employee job satisfaction is not good, many employees do not feel satisfied with their work if the work has to be done with people they don't like so that the employee's performance decreases and the work done takes a long time. The results of this research are as follows: Job Satisfaction has a positive and insignificant effect on Employee Performance with an original sample value of 0.066 and ap value of 0.273 > 0.05. Teamwork has a positive and significant effect on Job Satisfaction with an original sample value of 0.589 and ap value of 0.000 <0.05. Teamwork has a positive and significant effect on employee performance with an original sample value of 0.432 and ap value of 0.001 <0.05. Communication has a positive and significant effect on Job Satisfaction with an original sample value of 0.225 and ap value of 0.027 <0.05. Communication has a positive and significant effect on employee performance with an original sample value of 0.408 and ap value of 0.000 <0.05. Teamwork has a positive and insignificant indirect effect on Employee Performance through Job Satisfaction with an original sample value of 0.039 and ap value of 0.287. Communication has a positive and significant indirect effect on employee performance through job satisfaction with an original sample value of 0.015 and ap value of 0.292.